The Effect Of Compensation And Division Of Work On The Performance Of Integrated Islamic School Teachers In The Institution Under The Auspices Of The Amal Insan Mulia Foundation In Kulon Progo, With Motivation As An Intervening Variable - Astuti, Puji; Husainah, Nazifah; Hasanah, Hasanah (SEAN Institute, 2024)
The main factor supporting educational success is the teacher who has the main task of teaching. The compensation provided by the Foundation has a positive effect on improving teacher performance, as well as the division of work and motivation. The three variables are thought to be interconnected. Teachers are able to carry out their duties and responsibilities if these aspects can be fulfilled. Foundations play an important role in this matter. The research method was chosen using a quantitative method with a sample of Integrated Islamic School teachers at the Insan Mulia Charitable Foundation with data processing using smart PLS. The results obtained from this research are that compensation and division of work influence motivation and performance, and motivation has a significant influence on performance. Good compensation will have a positive influence on the performance of Integrated Islamic School Teachers at the Insan Mulia Kulon Progo Charitable Foundation. Teacher performance will be maximized with appropriate division of tasks. Motivation provided by superiors and colleagues can influence teacher performance because it is an encouragement to work better.